2011
DOI: 10.1248/cpb.59.947
|View full text |Cite
|
Sign up to set email alerts
|

Bisbenzylisoquinoline Alkaloids from Nelumbo nucifera

Abstract: From the embryos of the seeds of Nelumbo nucifera, three bisbenzylisoquinoline alkaloids, nelumboferine and nelumborines A and B, were isolated along with four known compounds, neferine, liensinine, isoliensinine and anisic acid. The structures of the new alkaloids were determined mainly by spectroscopic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 12 publications
2
48
0
Order By: Relevance
“…1). 10) We also found that neferine decreases locomotor activities in mice. 11,12) These results prompted us to synthesize nelumboferine and to evaluate its pharmacological activity.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…1). 10) We also found that neferine decreases locomotor activities in mice. 11,12) These results prompted us to synthesize nelumboferine and to evaluate its pharmacological activity.…”
mentioning
confidence: 56%
“…O-Methylneferine was prepared by methylation of neferine with trimethylsilyldizaomethane. 10) Synthesis of Nelumboferine Our synthesis plan is shown in Chart 1. Because nelumboferine is a dimer of benzylisoquinoline, it is synthesized by Ullmann coupling 15,16) of two chiral isoquinoline monomers (R)-5a (top half) and (R)-5b (bottom half).…”
Section: Resultsmentioning
confidence: 99%
“…The identified biologically active substances including liensinine, isoliensinine and neferine ( Fig. 1) are the three major alkaloids isolated from Lotus Plumule (Itoh et al, 2011;Yu et al, 2013). Recently, various studies have indicated that these bisbenzylisoquinoline alkaloids have beneficial pharmacological effects, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Neferine (Fig. 1), a bisbenzylisoquinoline alkaloid, is a major active component isolated from the green seed embryos [2]. Various studies have indicated that neferine has extensive pharmacological effects, including anti-hypertensive, anti-arrhythmic, sedative, and cholinesterase inhibitory actions [3,4].…”
Section: Introductionmentioning
confidence: 99%